An integrative framework for computational modelling of cardiac electromechanics in the mouse - Land, S (2013)
This thesis describes the development of a framework for computational modelling of electromechanics in the mouse, with the purpose of being able to integrate cellular and tissue scale observations in the mouse and investigate physiological hypotheses. Specifically, the framework is applied to interpret electromechanical coupling mechanisms and the progression of heart failure in genetically modified mice. Chapter 1 introduces the field of computational biology and provides context for the topics to be investigated. Chapter 2 reviews the biological background and mathematical bases for electromechanical models, as well as their limitations. In Chapter 3, a set of efficient computational methods for coupled cardiac electromechanics was developed. Among these are a modified Newton method combined with a solution predictor which achieves a 98% reduction in computational time for mechanics problems. In Chapter 4, this computational framework is extended to a multiscale electromechanical model of the mouse. This electromechanical model includes our novel cardiac cellular contraction model for mice, which is able to reproduce murine contraction dynamics at body temperature and high pacing frequencies, and provides a novel explanation for the biphasic force-calcium relation seen in cardiac myocytes. Furthermore, our electromechanical model of the left ventricle of the mouse makes novel predictions on the importance of strong velocity-dependent coupling mechanisms in generating a plateau phase of ventricular pressure transients during ejection. In Chapter 5, the framework was applied to investigate the progression of heart failure in genetically modified 'Serca2 knockout' mice, which have a major disruption in mechanisms governing calcium regulation in cardiac myocytes. Our modelling framework was instrumental in showing for the first time the incompatibility between previously measured cellular calcium transients and ventricular ejection. We were then able to integrate new experimental data collected in response to these observations to show the importance of beta-adrenergic stimulation in the progression of heart failure in these knockout mice. Chapter 6 presents the conclusions and discusses possibilities for future work.